The efficacy and tolerability of 10mg and 20mg/day isotretinoinin the treatment of acne vulgaris in Iraqi patients - Abdullah, Galawish A. (AL-Kindy College Medical Journal, 2013)
Back ground: Oral isotretinoin is recommended for sever nodulocystic acne in the doses 0.5- 2mg/kg/day which is usually associated with higher incidence of adverse effects. To reduce the incidence of side-effects and to make it more costeffective, the lower dose regimen of isotretinoin has been used. Aim: To compare the efficacy and tolerability of oral isotretinoin 10mg and 20mg/day in acne vulgaris. Methods: one hundred and twenty patients with acne vulgaris were randomized into two treatment regimens each consisting of 60 patients. The first was treated with 10mg/day and the second group with 20mg/day for 24 weeks. Fifty five patients from the first group and 47 patients from the second group who continued the study for 24 week and 8 weeks after cessation of therapy. The response rate was recorded in the form of acne load and acne grade initially, during treatment and after 8 from stopping treatment. Side effects were also recorded in both groups. Results: The response rate in both groups was comparable in mild, moderate, and severe acne vulgaris patients. Frequency and severity of treatment-related side-effects were significantly higher in the second group as compared to the first group. Conclusion: 10mg/dayisotretinoin can be used in the treatment of mild, moderate and severe acne with less side effects as compared to 20mg/day.